Online Learning in Pandemic Era with Edmodo Application on Excretory System Material - Rosdiana, Riski (Biosfer: Jurnal Tadris Biologi, 2021)
This research aims to describe the influence of Problem-Based Learning (PBL) with Edmodo on students' learning outcomes. The research design was Matching Pretest-Posttest Control Group Design. The research samples were the students of class XI MIA 3 and MIA 4 of SMAN 1 Pagerbarang Tegal. The researchers collected the data using tests and questionnaires. The analysis revealed that the PBL model with Edmodo In the excretory system material obtained an average percentage of 88% in meeting 1,  86% in meeting 2, and 88% in meeting 3. Furthermore, the average value of syntax 1 was 87%, syntax 2 was 98%, syntax 3 was 87%, syntax 4 was 86%, and syntax 5 was 88%. All syntaxes were in the moderate category except for the second syntax. There was an increase in the learning outcome between the experimental and control classes, where the experimental class scored higher than the control class